The Jumping Up (J-Up) Test: Making the Diagnosis of Acute Appendicitis Easier in Children. (November 2019) - Tzortzopoulou, Adelais K.; Giamarelou, Panagiota; Tsolia, Mariza; Spyridis, Nikolaos; Vakaki, Marina; Passalides, Alexander; Zavras, Nikolaos
We evaluate a new clinical test, jumping up (J-up) test, to diagnose easier appendicitis in children. A total of 407 patients, aged 5 to16 years, with right lower quadrant abdominal pain were asked to jump rising both hands and trying to reach a toy hanging down from the ceiling of the examination room. Bieri pediatric Face Pain Scale was used for recording the pain response. J-up test has sensitivity of 87% and specificity of 70%. A positive J-up test combined with leukocytosis (white blood cells count >12 000/mm 3 ), neutrophilia >75%, neutrophil/lymphocyte >2, and C-reactive protein >5 mg/dL, achieved a posttest probability of appendicitis of 85%. A negative J-up test combined with the aforementioned blood markers within normal range had a posttest probability for non-appendicitis of 92%. J-up test is a reliable clinical test, which could be used even by an inexperienced doctor. Combined with classical blood markers, it could successfully predict which child is in urgent need or not of surgery.